Optimization of Modeling Techniques for Economic Rstoration information systems after the Covid-19 pandemic by Simple Additive Weighting - Muhamad Muslih; Dea Kris Sintiana Putri; Eneng Siti Nasiroh; Raziya Mutasim; Novohatko Elena Nivolaevna; Jelita Asian (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2023)
The Covid-19 pandemic had a major impact on the world economy, including Indonesia. Rp. 677.2 Trillion is prepared by the Indonesian government for the recovery of this condition by providing assistance to business actors. Then eligibility of beneficiaries based on certain criteria is a complicated process, the aid process has an opportunity to make inaccurate decisions because the process of determining aid is based on subjectivity. It is likely that the selected business actors do not achieve the standards desired by the government. For this reason, a decision support system was developed that could perform the calculation process against all the criteria for determining beneficiaries. The Simple Additive Weighting (SAW) method which can be used in determining the eligibility of beneficiaries as a decision support system for the government. Business actors who will be selected to be eligible aid recipients have the criteria that have the highest ranking value that hasm been determined. The criteria needed are the criteria for not receiving people's business credit (KUR), the criteria for starting business capital, the criteria for having business information (SKU) and the criteria for not being a civil servant. Due to the large number of business actors who received this assistance, it made it difficult for the government to mminimize errors in providing assistance, so that quite a number of business actors received this assistance but did not comply with government criteria. The final results of this study found that the decision support system with the SAW method problem in determining the provision of method can produce the largest value with a weight of 1.00 which is selected as an alternative "Acceptable" and the smallest value is chosen as an alternative " Not Eligible to Receive "assistance with a calculation result of less than 0.500.